Integrated Crop–Livestock–Forest Systems With No-Till Can Restore Soil Organic Carbon Stocks in a Brazilian Ferralsol - Jolimar Antonio Schiavo; Valquiria Rodrigues Lopes; Alexandre Romeiro de Araújo; Manuel Claudio Motta Macedo; Naelmo de Souza Oliveira; Roseline da Silva Coêlho; Camila Beatriz da Silva Souza; Paulo Guilherme da Silva Farias; Elói Panachuki; Allan Motta Couto; Maren Oelbermann (Applied and Environmental Soil Science)
Crop–livestock–forest integration (CLFI) systems offer a promising approach to enhancing soil organic carbon (SOC) content within various aggregate size classes, thereby improving soil productivity and its capacity for atmospheric carbon (C) sequestration. This study aimed to assess SOC content across different water-stable aggregate size classes and its influence on aggregate formation in a Ferralsol under various long-term farming systems, including CLFI with pasture rotation (CLFI-PA), CLFI with crop rotation (CLFI-CR), conventional continuous cropping (CCC), permanent pasture without fertilization (PP-WoF), permanent pasture with fertilization (PP-WF), and the native Cerrado as a reference. All cropping systems evaluated in this study are managed under a no-till system, except for the CCC system. Undisturbed soil samples were collected from the 0.0- to 0.10-m layer to evaluate aggregate stability in water, SOC stocks, and SOC distribution across different soil aggregate classes. The geometric mean diameter (GMD) and mean weight diameter (MWD) were calculated. After 23 years of CCC, there was a 53% (12.94 Mg ha−1) reduction in SOC compared to the Cerrado (27.26 Mg ha−1), characterized by a predominance of microaggregates and significantly lower GMD and MWD values (p<0.05). The MWD and GMD values ranked as follows: Cerrado > PP-WoF > CLFI-PA > CLFI-CR > PP-WF > CCC. In the no-till systems, macroaggregates were predominant, with higher GMD and MWD values. The PP-WF, PP-WoF, CLFI-PA, and CLFI-CR systems showed SOC stocks of 25.70, 21.53, 21.40, and 20.38 Mg ha−1, respectively, with a positive correlation between SOC stocks and macroaggregates (p<0.05). The findings highlight the potential of CLFI systems to store carbon in the soil and promote macroaggregate formation, comparable to pastures established for 25 years and the native Cerrado.